Observers' Judgments of the Effects of Glare on Their Visual Acuity for High and Low Contrast Stimuli. (July 2016) - Sewall, Ashley A. Stafford; Borzendowski, Stephanie A. Whetsel; Tyrrell, Richard A.; Stephens, Benjamin R.; Rosopa, Patrick J.
Disability glare refers to a reduction in the ability to discern a stimulus that is positioned near another stimulus that has a much higher luminance. While it is common for drivers to report that they have been "blinded" by oncoming headlights, it is unclear whether observers can accurately judge when they are visually disabled by glare. This experiment sought to quantify the accuracy with which observers can judge when a glare source reduces their visual acuity. Seventeen observers estimated their disability glare threshold (DGT)—the luminance of a glare source that would be just sufficient to impair their ability to discern the orientation of a Landolt C that was surrounded by the glare source. These estimated DGTs were compared to the participant's actual DGTs. Participants consistently underestimated the intensity of glare that was required to impair their acuity. On average, estimates of glare threshold were 88% lower than actual glare threshold intensities. Participants' judgments were affected by stimulus size but not stimulus contrast. These results suggest that observers can exaggerate the debilitating effects of glare and that they can fail to appreciate that high contrast stimuli are more robust to glare. A driver who believes that even the lowest intensities of headlight glare can visually impair an oncoming driver may be reluctant to use high beam headlamps, despite their significant visibility advantages.